Lizards Are Important Hosts for Zoonotic Flavivirus Vectors, Subgenus Culex, in the Southern USA - Reeves, Lawrence E.; Burkett-Cadena, Nathan D. (Frontiers in Tropical Diseases, 2022)
Host association is among the most important factors that drive the transmission dynamics of mosquito-vectored pathogens. Competent vectors that feed exclusively upon non-competent hosts will not transmit pathogens, and highly competent hosts that are not bitten by competent vectors will not contribute to pathogen amplification. Therefore, characterizing the blood-feeding ecology of vector mosquitoes is critical to understanding how zoonotic pathogens amplify within ecosystems and spillover to humans and domesticated animals. In North America, mosquito species of the subgenus Culex are considered the most important vectors of zoonotic Flaviviruses, particularly West Nile virus (WNV), St. Louis encephalitis virus (SLEV), and western equine encephalitis virus. Many species of the Culex subgenus Culex are thought to feed predominantly upon birds and mammals, a behavior that facilitates the amplification and spillover of these zoonotic pathogens. Much of our understanding of the host associations of Culex vectors is based on research conducted in the 1960s and 1970s that used serological methods to infer host group(s). Here we reevaluate host associations of six Culex species from the southern US (Florida and Arizona) using DNA barcoding-based blood meal analysis. Our results demonstrate that reptiles, particularly lizards, constitute an important, and previously underappreciated, group of vertebrate hosts for several subgenus Culex mosquitoes. In Florida, >25% of Culex nigripalpus blood meals were derived from lizards (mainly Anolis spp.), and reptile host use generally increased from north to south with ~10%, ~25% and ~60% of Cx. nigripalpus blood meals derived from reptiles in northern, central, and southern Florida, respectively. In southern Arizona, lizards (mainly Sceloporus spp. and Urosaurus ornatus) constituted 40-45% of blood meals of Culex tarsalis, Culex thriambus, and Culex stigmatosoma. Other species of the subgenus Culex, including Culex quinquefasciatus, were not found to feed upon reptiles at the same sites, suggesting host association variation within Culex subgenus Culex. Whether or not lizards contribute to or dilute amplification of zoonotic Flaviviruses depends upon host competency of the lizard species bitten for WNV and SLEV. To date, very few studies have evaluated host competence of lizards for these viruses, so their roles in transmission cycles of zoonotic Flaviviruses remains obscure.